(untitled) (Global Journal of Management and Business Research, 2014)
The study assessed the level of compliance of construction professionals to ethical standards in the Nigerian construction industry. The study area was Lagos State and the target respondents were the registered professionals including architects, quantity surveyors, builders and engineers. A total of one hundred and seventy (170) questionnaire were randomly administered on the professionals and one hundred and thirty eight (138) were retrieved representing 81.18% response rate. Findings revealed that professionals displayed high level of compliance to clients service delivery with Mean Item Score (MIS) ranged between 3.22 to 3.79, educational and professional qualification MIS ranged 3.18 to 3.71 and standards of practice MIS ranged between 3.16 to 3.63. The overall rating revealed that professionals have highest level of compliance to standards of practice with 54.76%, while the least ranked ethical standards was fair compensation with 49.31%. ANOVA test established a statistical significant difference among the professionals view about compliance of the professionals to clients service delivery (F value=2.447, P value=0.020) and professional development (F value=3.774, P value = 0.001).